Antibacterial Screening of New Synthesis Schiff Base having Benzimidazole Moiety - Redayan, Muayed Ahmed; Hussein, Maha Salih; Lafta, Ashraf Tark (Asian Journal of Chemistry, 2017)
A new series of benzimidazole containing Schiff base moiety has been synthesized. The reaction was achieved through cyclocondensation reaction of the substituted 1,2-phenylenediamines and amino acids (glycine, alanine and tyrosine) to gave substituted benzimidazole derivatives 1(a-f). Condensation of these compounds with a variety of aromatic aldehyde yielded the new benzimidazole substituted Schiff base. The chemical structures of the synthesized compounds were confirmed by FT-IR, 1H NMR and 13C NMR. Selected compounds were tested in vitro for their antibacterial activity by disc diffusion method against two types of Gram-positive bacteria namely (Staphylococcous aureus, Bacillus subtilis) and Gram-negative bacteria namely (Pseudomonas aeruginosa, Escherichia coli). The results displayed that most of the prepared compounds have a good antibacterial activity in compared with the standard antibiotic ampicillin and ciprofloxacin.